PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS - Sari, Anggi Yulia; Anggraini, Villia; Jufri, Lucky Heriyanti (Universitas PGRI Sumatera Barat, 2021)
The purpose of this study was to determine whether there is an effect to the application of the Problem Based Learning (PBL) model to the mathematical problem solving ability of students of the sixth grade of MIPA SMAN 1 Six Lingkung. This type of research is PreExperimental Design, with research design that is Pre-test and Post-test Group.The population in this study were all students of class XI MIPA SMAN 1 Six Lingkung, which consisted of six classes.The sampling technique in this study used random sampling,with the sample of there search being the students of Class XI MIPA 6. The instruments used in this study were the Pre-test and Post-test given before and after applying Problem Based Learning (PBL). The analysis technique used is the t-test. The calculation results obtained by the value of t_count=4.99 with N=35, significant figure =0.05 and t_table=1,69, because t_count is greater than t_table then reject H_0. So it can be concluded that there is an influence of the application of the Problem Based Learning (PBL) model to the mathematical problem solving ability of students of class XI MIPA SMAN 1 Six Lingkung.